Searching for additional sources of inflation persistence: the micro-price panel data approach - Rafal Raciborski (National Bank of Belgium, 2008)
It is often argued that the baseline New-Keynesian model, which relies solely on the notion of infrequent price adjustment, cannot account for the observed degree of inflation sluggishness. Therefore it is a common practice among macro modellers to introduce an ad hoc additional source of persistence to their models. Yet, the empirical validity of this practice has never been formally tested. This paper attempts to examine whether there is some additional persistence present in the data on micro-prices, beyond that implied by infrequent price adjustment. We consider two distinct sets of assumptions consistent with the existence of an intrinsic or extrinsic source of sluggishness and build and estimate two alternative models based on these assumptions. It is shown that in he case of certain product categories, particularly food, there is evidence of less sluggishness than what the standard assumptions underlying the New-Keynesian model would imply. We find certain support for the existence of an additional source of sluggishness for some industrial goods and services. Importantly however, the results are sensitive to the choice of the model. We conclude that some inconsistencies with the baseline New-Keynesian assumptions may be tracked in the price behavior. Yet, it is too early to assess their strength or the effect on macro aggregates. Therefore, at the current stage it would be premature to discard the baseline version of the New-Keynesian model based on evidence from micro-data. Similarly, the micro support for introducing an extra source of inflation sluggishness to macro-models is still relatively weak
Keywords: C51; C81; E13; E1; D21; L11; 330; Price stickiness; inflation persistence; gradualism; Preisrigidität; Inflationsbekämpfung; Inflationssteuerung; Neoklassische Synthese; Belgien